IMPLEMENTATION OF PUBLIC-PRIVATE PARTNERSHIP IN THE FIELD OF EDUCATION IN UKRAINE AND ABROAD - Maslov, V. (Socio-economic relations in the digital society, 2022)
The global economic crisis has led to a decrease in the number of financial resources directed to the scientific and educational sphere of the national economy, although the most developed countries, including the EU countries, which have not reduced such funding, see this sector of the economy as a guarantee of ensuring high competitive status. Developed countries often use the financing of universities in order to subsidize the final recipients of competitive advantages – enterprises through the public-private partnership mechanism (PPP). The purpose of the study is to determine the peculiarities of the implementation of PPP mechanisms in Ukraine and abroad using comparative analysis methods. To achieve this goal, the article uses general scientific (analysis and synthesis) and specific (observation, description, graphic interpretation, grouping) methods of scientific research. The main results of the study include generalized and supplemented by the authors the main socio-economic interests of authorities, business and higher education institutions (HEI), which are implemented in PPP projects and ensure the development of higher education; improved typology of PPP development levels in the field of education; systematized state initiatives of some foreign countries in the development of the interrelationships of "HEI – business structure"; isolation of the main types and clusters of forms of interaction between higher education institutions and business structures in the world and domestic practice. The authors summarized and substantiated the most effective PPP models in the field of education in Ukraine and identified the main directions of cooperation between higher education institutions and the business environment in the model of PPP projects implementation. The practical value of the research results lies in the development of proposals for improving the effectiveness of partnerships between the higher education system and business structures.
Keywords: public-private partnership; financing models; higher education system; business environment; public-private partnership projects